Hymenoporus paradoxus gen. et sp. nov., a striking fungus of the family Omphalotaceae (Agaricales, Basidiomycota) with tubular hymenophore - Tkalčec, Zdenko; Mešić, Armin; Deng, Chun-Ying; Pleše, Bruna; Ćetković, Helena (Phytotaxa, 2015)
Hymenoporus paradoxus, a new marasmioid fungal species belonging to the new genus is described from southern China. It differs from all other marasmioid species by a true tubular hymenophore, a character previously unknown in marasmioid fungi, and from all other tubular agarics by a hymenophore attached to a free collarium, and central, tough, dark and filiform stipe. The additional diagnostic characters are small basidiocarps, mostly convex pileus, smooth, hyaline, non-amyloid spores, densely packed dendriform cheilocystidia, and pileipellis composed of repent hyphae densely covered with simple to coralloid excrescences, intermixed with dendriform cells. As peculiar morphological characters had indicated, molecular phylogenetic analyses based on the 28S rDNA sequences confirm phylogenetic position of the new species in Omphalotaceae and a need to establish a new genus. Color photographs of macro- and micromorphological characters, SEM microphotographs, and a phylogenetic tree based on the partial 28S rDNA gene are provided.